Factors associated with suicidality among school attending adolescents in morocco - Tom, Abdallah; Mahfoud, Ziyad R. (Frontiers in Psychiatry, 2022)
Suicide amongst adolescents is a growing epidemic accounting for 6% of all adolescent deaths. Even though 79% of adolescent suicides occur in low- and middle-income countries, where suicide is the second leading cause of death, research is relatively lacking. As such, we aim to gain a greater understanding of suicide in said countries by assessing ideation and planning and associated factors in Morocco. Global Schools Health Survey data was analyzed. Approximately 14.4% and 12.9% reported ideation and planning respectively during the prior year in 2016, indicating a decrease from the reported rates of ideation of 16.0% and 17.0% and planning of 14.6% and 15.0% in 2006 and 2010 surveys respectively. Increased ideation was found to be positively associated with identifying as female and increasing age, whereas planning was positively associated with a lower educational level and living in a rural area. Both were positively associated with increased hunger frequency. Several factors increased the likelihood of ideation: bullying, feeling lonely, current cigarettes smoking, and current marijuana use. Studying factors associated with suicide is challenging, alternatively, factors affecting ideation and planning can be assessed. Sociocultural differences may impact trends in a specific region, though countries in said region may have comparable trends. The study adds to the limited data available in the region. Reverse causality and under-reporting could be the main limitations of this study. Interventions considering those results should be tested to decrease such a prevalence.